Novel cardiac pacemaker-based human model of periodic breathing to develop real-time, pre-emptive technology for carbon dioxide stabilisation. Issue 1 (12th August 2014) - Baruah, Resham; Giannoni, Alberto; Willson, Keith; Manisty, Charlotte H; Mebrate, Yoseph; Kyriacou, Andreas; Yadav, Hemang; Unsworth, Beth; Sutton, Richard; Mayet, Jamil; Hughes, Alun D; Francis, Darrel P
Abstract : Background: Constant flow and concentration CO2 has previously been efficacious in attenuating ventilatory oscillations in periodic breathing (PB) where oscillations in CO2 drive ventilatory oscillations. However, it has the undesirable effect of increasing end-tidal CO2, and ventilation. We tested, in a model of PB, a dynamic CO2 therapy that aims to attenuate pacemaker-induced ventilatory oscillations while minimising CO2 dose. Methods: First, pacemakers were manipulated in 12 pacemaker recipients, 6 with heart failure (ejection fraction (EF)=23.7±7.3%) and 6 without heart failure, to experimentally induce PB. Second, we applied a real-time algorithm of pre-emptive dynamic exogenous CO2 administration, and tested different timings. Results: We found that cardiac output alternation using pacemakers successfully induced PB. Dynamic CO2 therapy, when delivered coincident with hyperventilation, attenuated 57% of the experimentally induced oscillations in end-tidal CO2 : SD/mean 0.06±0.01 untreated versus 0.04±0.01 with treatment (p<0.0001) and 0.02±0.01 in baseline non-modified breathing. This translated to a 56% reduction in induced ventilatory oscillations: SD/mean 0.19±0.09 untreated versus 0.14±0.06 with treatment (p=0.001) and 0.10±0.03 at baseline. Of note, end-tidal CO2 did not significantly rise when dynamic CO2 was applied to the model (4.84±0.47 vs 4.91± 0.45 kPa, p=0.08). Furthermore, mean ventilation was also not significantly increased by dynamic CO2 compared with untreated (7.8±1.2 vs 8.4±1.2 L/min, p=0.17). Conclusions: Cardiac pacemaker manipulation can be used to induce PB experimentally. In this induced PB, delivering CO2 coincident with hyperventilation, ventilatory oscillations can be substantially attenuated without a significant increase in end-tidal CO2 or ventilation. Dynamic CO2 administration might be developed into a clinical treatment for PB. Trial Registration number: ISRCTN29344450.